Delimitation of co-perpetration from aiding and abetting in the criminal offence of robbery - Mijanić, Vedran (Array, 2020)
Analysis of the case law related to the prosecution of the criminal offense of robbery. Robbery is a complex criminal offense committed when a perpetrator uses force against another person, as well as when they threaten to directly endanger one's life or cause physical injury, or when they seize another's movable property with the aim of misappropriating it. Methods: In selected cases, the application of main theories regarding complicity was examined and critically tested, taking into account the findings of the fact. Results: The analysis of the current case law points to the absence of clear criteria for the delimitation of complicity from aiding and abetting in the criminal offense of robbery. Criminal law theory leaves too much empty space subject to manipulation when, by mentioning substantial contribution, it refers to behaviors without which an offense could not have been committed in the planned manner. The will of the perpetrator should constitute a secondary tool to be used only in controversial, borderline situations, where the nature of the behavior not pertaining to the essence of the criminal offense, due to its character and importance within the joint plan, requires it to be equated with the perpetration act. In that regard, as the joint plan is not a term that can be fully objectified since the importance of roles within the plan can vary from one group of perpetrators to another, assessing the will of the perpetrator can be an alternative to resort to in situations where it is not possible to evaluate the quality of a behavior based on objective rules. Conclusion: Uneven case law in the evaluation of the behavior of individual participants in robbery contributes to the inequality of citizens before the law and endangers legal security – one of the foundations of the rule of law.